2022
DOI: 10.1016/j.ekir.2021.10.007
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Scoring System Based on Oxford Classification Indicating Steroid Therapy Use for IgA Nephropathy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…Previous studies indicated a poor renal prognosis for patients with IgA nephropathy who had a rapidly progressive course, tubular atrophy, or MPGN-like changes [ 13 , 27 , 28 ]. One multicenter cohort study of 113 Chinese patients with crescentic IgA nephropathy showed that approximately 70% of patients developed end-stage renal disease within 5 years, regardless of immunosuppressive therapy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated a poor renal prognosis for patients with IgA nephropathy who had a rapidly progressive course, tubular atrophy, or MPGN-like changes [ 13 , 27 , 28 ]. One multicenter cohort study of 113 Chinese patients with crescentic IgA nephropathy showed that approximately 70% of patients developed end-stage renal disease within 5 years, regardless of immunosuppressive therapy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The initial serum creatinine level strongly predicted ESKD, as > 95% of patients with initial serum creatinine > 6.8 mg/dL developed ESKD during follow-up. Another cohort study of 858 Japanese patients with IgA nephropathy demonstrated a poor response to steroid therapy in patients with renal tubular atrophy [ 27 ]. One study of 27 patients with IgA deposition on immunofluorescence and MPGN features found a poor renal prognosis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…T2 lesions have indeed been associated with the absence of response to glucocorticoids in both Asian and Caucasian cohorts. 92,93 The therapeutic responsiveness of S1 lesions is more controversial. A proportion of patients with S1 lesions respond clinically and pathologically to glucocorticoids, 93,[96][97][98] supporting the existence of a specific form of podocytopathy in some IgA nephropathy patients.…”
Section: Histologic Datamentioning
confidence: 99%
“…92,93 The therapeutic responsiveness of S1 lesions is more controversial. A proportion of patients with S1 lesions respond clinically and pathologically to glucocorticoids, 93,[96][97][98] supporting the existence of a specific form of podocytopathy in some IgA nephropathy patients. These observations have led to an updated recommendation of the Oxford classification to subclassify S1 lesions according to the presence of signs of podocyte damage, such as podocyte hypertrophy or tip lesions.…”
Section: Histologic Datamentioning
confidence: 99%
“…While other studies have also explored the impact of immunosuppressants on kidney outcomes according to the presence and extent of crescents [ 6 , 7 ], Itami et al . extended the use of kidney histology in individualizing the decision for immunosuppressants by developing the steroid responder score (SRS) and steroid nonresponder score (SNRS) [ 8 ]. Among Japanese patients with IgAN, immunosuppression with steroids for high SRS (presence of three or more of the M, E, S and C components of the Oxford MEST-C score) improved renal survival.…”
mentioning
confidence: 99%